(untitled) (Raparin Journal of Humanities (RJH), 2022)
This research, tagged with (The Reasons for the Selection of Vocabularies and Forms in the Interpretations of Surat Al-Araf - Selected Models) seeks to highlight the beauty of accuracy in choosing the pronunciation, the splendor of selecting words and formulas, and the uniqueness of their use in the Noble Qur’anic expression, and since that was based on the beautiful expressive word and influential words, we focused the explanation on this, The important aspect, let’s stand on the accuracy of choosing the vocabulary and formulas of this unique divine discourse, and what it stores of the features of uniqueness and creativity, and what God Almighty has deposited in it of secrets, subtleties and indications, and we have tried to be careful to fulfill it in this study, and what it required of a full roaming between the folds of interpretations and books The sciences of the Qur’an, in search of the clues, the beauty of the matter and the opinions expressed by the great scholars, and in view of this influential impact, and the remarkable beauty, we stand in our analysis of the topic (the beauty of the Qur’anic vocabulary and formulas) and from God the success. ‏